Preparation method of cavings cellulose nanocrystal and application of cavings cellulose nanocrystal in Pickering emulsion

By pulverizing, alkali washing, enzymatic decomposition, bleaching, acidolysis and dialysis of the glutinous bran, and using ultrasonic technology to reduce the cellulose size to the nanoscale, the problem of low recycling rate of millet bran is solved, and the efficient preparation of glutinous bran cellulose nanocrystals is achieved, and the stability and phenol loading capacity of glutinous bran is achieved in Pickering emulsion.

CN119874946APending Publication Date: 2025-04-25SHANDONG ACADEMY OF AGRICULTURAL SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510092280.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The recycling rate of millet bran is not high, resulting in waste of resources and environmental pollution. The existing research mainly focuses on the research of lipids and dietary fiber, while there are few research on nanocellulose.

Method used

A method for preparing a glutinous cellulose nanocrystal is provided, including crushing, alkali washing, enzymatic lysis, bleaching, acidolysis and dialysis treatment, and reducing the cellulose size to the nanoscale by sonication.

Benefits of technology

The prepared glutinous cellulose nanocrystals have nanoscale size and high crystallinity, which can effectively stabilize the Pickering emulsion and show high loading rate and excellent load-bearing capacity when loading pyramophenol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874946A_ABST
    Figure CN119874946A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of biomass materials, and particularly relates to a preparation method of cavings cellulose nanocrystals and application of the cavings cellulose nanocrystals in Pickering emulsion. The method comprises the following steps: carrying out alkali washing treatment on bran coat and then carrying out enzymolysis; and hydrolyzing the obtained cavings cellulose in a sulfuric acid solution, and carrying out ultrasonic treatment on the hydrolyzed cellulose suspension to obtain the cavings cellulose nanocrystal. According to the preparation method provided by the invention, the prepared cavings cellulose nanocrystals can reach the nanoscale in size, small in fiber size, high in crystallinity and good in emulsion stabilizing capacity, functional groups of cellulose can be changed through different treatments, and when the cavings cellulose nanocrystals are used as an emulsion stabilizer, stabilization of Pickering emulsion is facilitated; the preparation method provided by the invention is simple and easy to operate, and the product yield is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomass materials, and specifically relates to a method for preparing rice bran cellulose nanocrystals and application of the nanocrystals in Pickering emulsions. Background Art

[0002] Millet is a plant of the genus Setaria in the Poaceae family. It is an important food crop that originated in the Yellow River Basin. Millet is widely planted in China and has the largest output in the world, accounting for 80% of the world's millet output. In addition, it is also planted in small quantities in Australia, the United States, Canada, France, North Korea, Japan, Hungary and other countries. Millet has strong adaptability and is drought-resistant and insect-resistant. Therefore, it is widely planted in some water-scarce areas such as Gansu, Shaanxi, Inner Mongolia and other places. In recent years, as people's economic level continues to improve, their diet tends to be more healthy and pure natural food. Millet has a balanced ratio of nutrients and a high digestibility of more than 90%. At present, there are more and more research reports on millet, which is a production crop with great potential. The nutritional value of millet is very rich, with a protein content of 9.28-15.8%, a carbohydrate content of about 70%, and a fat content of 3.8-5.2. Millet has a high vitamin content and is a good health food. The content of vitamin E in millet is between 39.66μg / g and 95.84μg / g, the content of vitamin B1 and B2 is 0.11mg / 100g and 0.12mg / 100g respectively, and the content of carotenoids is between 1.10μg / g and 19.55μg / g. The content of selenium in grains is very high, at 0.0533μg / g, which is higher than the prescribed standard. Millet has storability because of its low original moisture content and the protection of the husk, which isolates millet from the external environment.

[0003] Millet bran is the by-products such as bran, endosperm, millet residue and millet germ produced when millet is processed into millet. my country is the origin of millet cultivation and has a long history of cultivation. Its planting area is large and the annual output is very large. Therefore, the amount of millet bran produced is also large, about 400,000 tons per year. At present, there are relatively few studies on millet bran protein at home and abroad, which needs to be developed and utilized. Due to the different technical means of millet processing and the different origins of millet, there are some slight differences in the ingredients of millet bran. Under normal circumstances, the bran contains protein (15%), fat (3-8%), carbohydrates (16%-22%), water (10%), calories (125.1KJ / g), and also contains nutrients such as cellulose, polysaccharides, dietary fiber, vitamins, mineral elements, thiamine, riboflavin, niacin and various unsaturated fatty acids.

[0004] At present, the research on millet bran mainly focuses on the lipids and dietary fiber it contains. Wei Fuxiang et al. used supercritical extraction technology to extract millet bran oil from millet bran. The millet bran oil extracted by supercritical extraction was tested to contain high levels of unsaturated fatty acids, especially linoleic acid, which is as high as 67.8%. Linoleic acid helps to lower serum cholesterol and inhibit the formation of arterial thrombus, so it has a good effect in preventing cardiovascular diseases such as atherosclerosis and myocardial infarction. With the rapid development of social economy and the gradual improvement of consumers' requirements for quality of life, the processing and utilization of agricultural products have received more attention from the food industry. However, while the output and demand of agricultural products have increased significantly, a large amount of agricultural product processing waste has not received widespread attention, which has had a huge impact on resource waste and environmental pollution. In order to further realize the rationalization of resources, the high-value utilization of agricultural product processing waste is of great significance. Millet bran contains rich nutrients and natural active substances, and has broad application prospects in high-value utilization. The long-term recycling rate of millet bran is not high, and the accumulation of millet bran will cause environmental pollution and waste of resources. At present, most of the research on millet bran focuses on lipids, proteins and dietary fiber in millet bran, but there is not much research on nanocellulose.

[0005] Millet bran contains many active ingredients, but the recycling rate is not high. The accumulation of millet bran will cause environmental pollution and waste of resources. At present, most of the research on millet bran focuses on the lipids, proteins and dietary fiber in millet bran, but there is not much research on nanocellulose. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing rice bran cellulose nanocrystals.

[0007] Another object of the present invention is to provide the use of the above-mentioned rice bran cellulose nanocrystals in Pickering emulsion.

[0008] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: The present invention provides a method for preparing rice bran cellulose nanocrystals, comprising the following steps: (1) crushing and sieving the bran, washing the bran powder with ethanol, and then rinsing and drying to obtain treated bran powder; adding the bran powder to a NaOH solution, stirring, then filtering and collecting the precipitate, washing the precipitate with deionized water, and after the alkaline washing, drying the precipitate to obtain bran particles; (2) Resuspending the bran particles in distilled water; then, adding α-amylase at a ratio of 1:20 (m / v) and stirring at room temperature; after starch hydrolysis, after adjusting the pH to 11, adding alkaline protease, heating and stirring, centrifuging the mixture to collect particles, washing with distilled water to obtain an alkaline washed precipitate; adding the dried alkaline washed precipitate to a bleaching solution for bleaching; after the bleaching is completed, filtering and collecting the precipitate, and finally repeatedly washing and filtering with deionized water until the pH of the filtrate is neutral, and drying to obtain bran cellulose; (3) Weighing purified rice bran cellulose, dispersing it in a sulfuric acid solution according to a solid-liquid ratio, and hydrolyzing it; after the hydrolysis is completed, immediately terminating the reaction; removing the supernatant by centrifugation to collect the precipitate, then dialyzing it, and then diluting it with purified water to obtain a cellulose suspension; (4) Take a cellulose suspension, insert a titanium metal ultrasonic probe into the cellulose suspension, and perform ultrasonic treatment to obtain rice bran cellulose nanocrystals.

[0009] Furthermore, in step (1), the solid-to-liquid ratio of the bran powder to ethanol is 1:20; the drying temperature is 60°C; the solid-to-liquid ratio of the bran powder to the NaOH solution is 1:10 (w / v); the concentration of the NaOH solution is 4% (w / v); the stirring treatment is continuous stirring for 2 hours in a 90°C water bath environment; and the drying temperature is 50°C.

[0010] Furthermore, in step (2), the bran particles are resuspended in 80°C distilled water for 1 hour; the ratio of the bran particles to α-amylase is 1:20 (m / v); the concentration of the α-amylase is 0.6% (w / v); the stirring time at room temperature is 3 hours; after starch hydrolysis, the pH is adjusted to 11; the amount of alkaline protease added is 0.03% (w / w) of the weight of the bran particles; the specification of the alkaline protease is 200 U / mg; and the heating stirring is stirring at 80°C for 1 hour.

[0011] Furthermore, in step (2), the composition of the bleaching solution is: 1.7% (w / v) NaClO, 2.7% (w / v) NaOH, 7.5% (v / v) glacial acetic acid, and the remainder water; the solid-liquid ratio of the alkaline washing precipitate to the bleaching solution is 1:25 (w / v); and the bleaching treatment is carried out by continuously stirring in a water bath environment at 80°C for 2 hours.

[0012] Furthermore, in step (3), the ratio of the rice bran cellulose to the sulfuric acid solution is 1:15 (w / v); and the mass concentration of the sulfuric acid solution is 62%.

[0013] Furthermore, in step (3), the hydrolysis is carried out at 45°C for 30 minutes; the centrifugation is carried out at 8000 r / min for 10 minutes; and the dialysis is carried out at a molecular weight of 8000-14000.

[0014] Furthermore, in step (4), the concentration of the cellulose suspension is 0.3%, w / v; the diameter of the titanium metal ultrasonic probe is 15 mm; the conditions of the ultrasonic treatment are: in an ice water bath, the ultrasonic power is 150-600 W, the ultrasonic time is 60 min, and the ultrasonic process is started for 1 s and stopped for 1 s.

[0015] The present invention also provides rice bran cellulose nanocrystals prepared by the above preparation method.

[0016] The present invention also provides application of the above-mentioned rice bran cellulose nanocrystals in Pickering emulsion.

[0017] The present invention also provides the use of the above-mentioned rice bran cellulose nanocrystals in preparing a paeonol-loaded Pickering emulsion.

[0018] The beneficial effects of the present invention are: (1) The preparation method provided by the present invention can prepare the bran cellulose nanocrystals with a size of nanometer level, a small fiber size and a high crystallinity, and has a good ability to stabilize emulsions. Moreover, the functional groups of cellulose can be changed through different treatments, and when used as an emulsion stabilizer, it is beneficial to the stability of Pickering emulsions. (2) The cellulose nanocrystals prepared by the present invention are used to prepare a Pickering emulsion loaded with paeonol, which has a high paeonol loading rate and excellent carrying capacity; and the rapid oil decomposition rate of the 450W emulsion system helps to accelerate the release of paeonol in the oil phase and the transmission in the mixed micelles; (3) The preparation method provided by the present invention is simple and easy to operate, and has a high product yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The preparation process and physical diagram of cellulose; Figure 2 This is the particle size diagram of cellulose after acid hydrolysis and ultrasound; Figure 3 This is the zeta potential diagram of rice bran cellulose nanocrystals; Figure 4 Atomic force microscopy (AFM) (top) and transmission electron microscopy (TEM) (bottom) images of rice bran cellulose nanocrystals; Figure 5 This is the infrared spectrum after acid hydrolysis and ultrasound; Figure 6 X-ray diffraction patterns (upper) and crystallinity (lower) of cellulose after acid hydrolysis and ultrasound; Figure 7 The loss modulus (upper) and storage modulus (lower) of cellulose under four ultrasonic conditions; Figure 8 The thermogravimetric curve of cellulose (A), differential weight (B) and the final residual percentage diagram (C); Fig. 9 The change of static water contact angle of cellulose before and after ultrasound; Fig.10 Photos of fresh emulsions with different cellulose concentrations; Fig.11 Microscope images of fresh emulsions with different cellulose nanocrystal concentrations; Fig.12 is the change of droplet size of emulsions with different cellulose concentrations; Fig.13 Photos of fresh emulsions with different cellulose concentrations (top) and stored at room temperature for 15 days (bottom); Fig.14 Figure 1 shows the particle size of emulsions with different oil-water ratios (A), photos of fresh emulsions (B), and photos of emulsions after 15 days (C); Fig.15 Figure 1 shows the particle size of cellulose emulsions treated with different ultrasounds (A), photos of fresh emulsions (B), and photos of emulsions treated with different ultrasounds after 15 days (C); Fig.16 The effect of ion concentration on emulsion particle size (A) and Zeta potential (B); Fig.17 The effect of pH on the particle size (A) and Zeta potential (B) of the emulsion; Fig.18 The effect of temperature on the particle size (A) and Zeta potential (B) of the emulsion; Fig.19 The effect of storage time on the retention rate of paeonol; Fig. 20 Changes in bioavailability of paeonol in different emulsions. DETAILED DESCRIPTION

[0020] The technical scheme of the present invention is further explained and illustrated by specific embodiments below. The preparation method provided by the present invention obtains bran cellulose through crushing, alkali washing, enzymolysis, bleaching, acid hydrolysis, and dialysis treatment. The above steps can significantly remove most of the lignin and hemicellulose, and can effectively reduce the size of cellulose. However, the size of the obtained cellulose is still at the micron level, and further treatment is required to reduce the size of the cellulose. The specific process is as follows Figure 1 shown.

[0021] Example 1 (1) Purification and extraction of nanocellulose The bran was crushed and passed through an 80-mesh sieve. The bran was repeatedly washed with ethanol at a solid-liquid ratio of 1:20, then rinsed and dried at 60°C. The bran powder was added to a 4% (w / v) NaOH solution at a solid-liquid ratio of 1:10 (w / v), stirred continuously for 2 hours in a 90°C water bath, and then filtered to collect the precipitate. The precipitate was washed with deionized water to remove excess alkali solution. This alkali washing process was repeated twice. After the alkali washing, the precipitate was placed in a 50°C oven to dry overnight. The collected particles were resuspended in distilled water at 80°C for 1 hour; then, 0.6% (w / v) α-amylase (4000U / g) was added at a ratio of 1:20 (m / v) and stirred at room temperature for 3 hours. After starch hydrolysis, 0.03% (w / w) alkaline protease was added in sequence after the pH was adjusted to 11, and stirred at 80°C for 1 hour. The mixture was centrifuged to collect the particles and washed three times with distilled water. Then, bleaching treatment was carried out, and the dried alkaline washed precipitate was added to the bleaching solution at a solid-liquid ratio of 1:25 (w / v). The composition of the bleaching solution was: 1.7% (w / v) NaClO, 2.7% (w / v) NaOH, 7.5% (v / v) glacial acetic acid. Stirring was continued for 2 hours in an 80°C water bath environment, and then the precipitate was collected by filtration. This rinsing process was repeated twice, and finally, the filtrate was repeatedly washed and filtered with deionized water until the pH of the filtrate was neutral, and then dried in a 50°C oven.

[0022] Weigh the purified bran cellulose and disperse it in a 62% sulfuric acid solution at a solid-liquid ratio of 1:15 (w / v), and hydrolyze it in a 45°C water bath for 30 minutes. After the hydrolysis is completed, the reaction is immediately terminated with 10 times deionized water. Centrifuge (8000r / min, 10min) to remove the supernatant and collect the precipitate, then dialyze at a molecular weight of 8000-14000, and store it at 4°C for later use.

[0023] (2) Preparation of cellulose nanocrystals 200 mL of diluted cellulose suspension (0.3%, w / v) was placed in a 250 mL beaker, and a 15 mm diameter titanium ultrasonic probe was inserted into the suspension, about 20 mm from the liquid surface. The ultrasonic power was then adjusted to 150 W, 300 W, 450 W, and 600 W, and ultrasonic treatment was performed for 30 min, with the ultrasonic process starting for 1 s and stopping for 1 s. In order to prevent the cellulose suspension from overheating, the suspension was placed in an ice water bath to obtain cellulose nanocrystals.

[0024] Example 2 1. Particle size of cellulose nanocrystals The cellulose nanocrystal suspension prepared in Example 1 was diluted to 0.01%, and the particle size was analyzed using dynamic light scattering technology. Deionized water was used as the dispersion medium, and the sample was ultrasonically treated before measurement to fully disperse the sample. The refractive index of cellulose was 1.475, and the refractive index of the dispersant was 1.333, and each measurement was performed three times.

[0025] 2. Characterization of cellulose nanocrystal morphology The morphology of cellulose nanocrystals was observed using an atomic force microscope. The cellulose nanocrystal suspension was diluted to 0.001% with deionized water, mixed, and 10 μL of the dilution was carefully dripped onto the mica sheet and dried naturally at room temperature. The mica sheet was dried and the morphology was observed. The sample was scanned and recorded using the atomic force microscope rapid scanning system, and then the data was processed using the NanoScopeAnalysis analysis software.

[0026] (III) Zeta potential analysis The zeta potential of cellulose nanocrystal suspension was measured using a multi-angle particle size and high-sensitivity Zeta potential analyzer. Before measurement, the cellulose nanocrystals were diluted to 0.03% and dispersed evenly, and the measurement was performed three times each time.

[0027] (IV) X-ray diffraction (XRD) measurement XRD was used to analyze the crystallinity of cellulose nanocrystals. The powder sample was spread over the sample slot and measured under the conditions of a scanning range of 3°~50° and a scanning speed of 1° / min. The cellulose crystallinity (CrI) was obtained by the following formula: CrI(%)=(I002-Iam)I002×100 Where I002 represents the intensity value of the crystalline region and the non-crystalline region, and Iam represents the intensity value of the non-crystalline region.

[0028] (V) Fourier transform infrared spectroscopy (FTIR) determination Fourier transform infrared spectroscopy was used to measure the changes in chemical groups of cellulose nanocrystals. The sample was mixed and ground with potassium bromide at a ratio of 1:50 (w / w), and then pressed into tablets. The infrared wavelength range was 400-4000 cm-1.

[0029] 6. Rheological properties of suspension A portion of the sample was extracted from an appropriate number of samples and placed on the base surface of the rheometer. The rheological properties of the nanocellulose suspension were evaluated using a 40 mm plane at an ambient temperature of (25.0 ± 0.1) °C. During this process, the shear rate was set in the range of 0 to 100 s -1, in this way, the surface viscosity of the suspension is calculated. In order to study the dynamic flow phenomenon, the frequency of 1 Hz is locked, and then the viscoelastic region of the line is confirmed according to the strain change (0.01% to 100%). Then, while keeping the strain constant at 0.5%, the angular frequency is adjusted (0.1 to 100 rad / s) to observe the dynamic rheological performance of the suspension.

[0030] 7. Static water contact angle The wettability differences of cellulose nanocrystals of different lengths were analyzed by static water contact angle. The suspension of cellulose nanocrystals was formed into a film on the surface of an aqueous organic filter membrane by vacuum filtration, and then the membrane was dried at room temperature and pressure. Subsequently, an optical contact angle device equipped with a high-speed camera was used for photographic analysis. A 2μL drop of deionized water was gently placed on the surface of the film using a high-precision syringe. After balancing for 2 minutes, the camera recorded the balanced image, and the analysis software recalculated the contact angle value. The roughness of the cellulose nanocrystal film was measured using an atomic force microscope.

[0031] (VIII) Thermogravimetric analysis of cellulose Weigh a certain amount of rice bran nanocellulose suspension and freeze it in a -80℃ refrigerator. After freezing, dry it in a freezer dryer. Weigh 10 mg of the freeze-dried sample, put it in an aluminum oxide crucible, cover it, and analyze it with a synchronous thermal analyzer. The entire experiment was carried out under nitrogen protection, with a heating range of room temperature to 600℃, a heating rate of 10℃ / min, and a protective gas flow rate of 40 ml / min.

[0032] Results and Analysis: (1) The prepared cellulose was subjected to ultrasonic treatment at 150W for 30min. The particle size and zeta potential of the cellulose after ultrasonic treatment were measured. Figure 2 and Figure 3 As shown in the figure, the length of cellulose is about 270nm, reaching the nanometer level. The Zeta potential is about -30MV, which has good stability.

[0033] (2) Effect of ultrasonic treatment on cellulose size After ultrasonic treatment, the size and morphology of cellulose nanocrystals changed significantly. Figure 2 As shown in the figure, after 150W and 30min ultrasonic treatment, the length of cellulose decreased significantly from 7000nm to 300nm. This shows that ultrasonic treatment can effectively change the size of cellulose to the nanometer level.

[0034] In order to accurately analyze the effect of different ultrasonic conditions on cellulose size, cellulose samples were treated with different ultrasonic powers (150 W, 300 W, 450 W and 600 W) for 30 min. The particle size of the cellulose after ultrasonic treatment was then analyzed. The experimental results showed that with the gradual increase of ultrasonic power, the particle size of cellulose gradually decreased from the initial approximately 270 nm to approximately 120 nm.

[0035] like Figure 4 The atomic force microscopy (AFM) and transmission electron microscopy (TEM) observation results shown further confirmed that the nanocellulose after ultrasonic treatment exhibited an elongated needle-like structure and its size reached the nanometer level.

[0036] (3) Effects of acid hydrolysis and ultrasonic treatment on functional groups of nanocellulose Infrared spectroscopy was used to study the changes in functional groups in nanocellulose particles of different lengths obtained by homogenization. Figure 5 As shown. Broad absorption peaks at 3400~3300cm-1 and 1630~1640cm-1 were observed in all samples, which correspond to the stretching and bending vibrations of -OH groups, respectively. The peak at 2920cm-1 is attributed to the stretching of CH aliphatic bonds. Compared with untreated cellulose, a peak at 1400 cm-1 can be observed in all samples. -1 The peak at 900 cm-1 is related to the symmetrical bending of CH2 in the polysaccharide and the bending vibration of the CH group of the aromatic ring. −1 There is a small peak at , which corresponds to the CH rock vibration of cellulose. This may be due to the removal of components such as lignin by the alkali and bleaching process, releasing cellulose fibers surrounded by lignin. Comparing the FTIR spectra of acid hydrolyzed samples and nanocellulose samples of different lengths, it was found that there was no obvious difference between the spectra. This means that ultrasonic treatment cannot change the functional groups of nanocellulose.

[0037] (4) Effect of acid hydrolysis on cellulose crystallinity The X-ray diffraction patterns of cellulose obtained under different ultrasonic powers are shown in Figure 6. All diffraction patterns consist of amorphous broad humps and crystalline peaks. The obvious peaks of bran cellulose at 2θ = 16.5° and 22.0° are considered to be cellulose type I. Ultrasonic treatment did not change the type of cellulose. However, the peak intensity at 22.0° decreased with increasing ultrasonic power. This peak intensity is closely related to the crystallinity index (CrI) of cellulose. Compared with acid-hydrolyzed cellulose, the crystallinity of all samples decreased after ultrasonic treatment, and higher ultrasonic power resulted in a greater decrease in crystallinity. The crystallinity value of cellulose treated with 600W for 30min dropped to 60%. The reason for this decrease in cellulose crystallinity comes from the strong cavitation force generated by ultrasonic treatment, which causes the long cellulose particles to decompose into short cellulose nanoparticles and the collapse of part of the crystal structure. These results show that highly crystalline nanocellulose has been successfully extracted from bran.

[0038] (5) Interfacial shear rheology of nanocellulose treated with different ultrasound Frequency rheological measurements of cellulose, such as Figure 7 As shown in the figure, the loss modulus of cellulose increases slowly, while the storage modulus increases rapidly first and then increases slowly. When the frequency is 40 rad / s, the storage modulus of 150 W cellulose begins to decrease, while the storage moduli of 300 W, 450 W and 600 W are relatively stable, indicating that the interfacial modulus strength formed by them is higher. In contrast, the interfacial film formed by 450 W cellulose has higher toughness. Therefore, 450 W cellulose was used for subsequent emulsion preparation tests.

[0039] (6) Effect of ultrasonic treatment on the thermogravimetric properties of cellulose Determine the thermogravimetric curve of cellulose. Figure 8 The starting, ending, mass loss and maximum degradation temperatures are given. For all samples, a slight weight loss was observed below 100°C, which is attributed to the evaporation of bound water in cellulose. The peak at about 350°C reflects the decomposition process of cellulose. Next, the gradual decomposition reaction from 400°C to 530°C is about the release of oxygen from carbon elements. The decomposition peak of cellulose after ultrasonic treatment appears at around 230°C, which is lower than the decomposition peak without ultrasonic treatment. This may be because ultrasonic treatment reduces the size of cellulose, resulting in a higher surface area exposed to heat, which also leads to a decrease in the thermal stability of cellulose. As the temperature exceeds 350°C, the thermal stability of nanocellulose crystals is better than that of cellulose that has not been ultrasonically treated, and the final residual weight ratio of ultrasonic nanocellulose is also higher than that of cellulose without ultrasonic treatment, which proves that nanocellulose crystals have higher stability in high temperature environments.

[0040] (7) Effect of ultrasonic treatment on the static water contact angle of nanocellulose The static water contact angle of cellulose nanoparticle films was measured to reveal the changes in the wettability of nanocellulose after ultrasonic treatment. Fig. 9 As shown in the figure, it is obvious that ultrasound reduces the size of nanocellulose and also changes the contact angle of nanocellulose. The contact angle value of nanocellulose obtained after acid hydrolysis is 43.02°, indicating that the particles show low hydrophobicity. After ultrasonic treatment of cellulose, the contact angle value of cellulose particles increases. This shows that ultrasonic treatment can improve the hydrophobicity of cellulose nanoparticles and improve the wettability of particles. After ultrasonic treatment at 150W for 30min, the contact angle of the prepared nanocellulose reached 48.25°, showing high hydrophobicity. With the increase of ultrasonic power, the contact angle of cellulose also increases. In the water-oil mixed environment, their hydrophobic crystal faces directly touch the interface, enabling them to be attracted to the oil-water separation layer. However, this (200) β crystal face mainly exists at the edge of the cellulose crystal, while the cellulose surface is mainly hydrophilic. When using ultrasonic treatment, due to the cavitation effect generated, the long cellulose nanoparticles can be broken into short rod-shaped nanoparticles, and some crystal structures may be damaged.

[0041] Example 3 Preparation of Cellulose Nanocrystal Stabilized Pickering Emulsion Cellulose nanocrystals were dispersed in deionized water at different mass fractions (0.2%, 0.4%, 0.6%, 0.8%, 1.0%), and the corresponding bran oil was added at an oil-water ratio of 5:5, and then sheared at 10000r / min for 3min in a high shear emulsifier and homogenized at 20MPa for 2min. The Pickering emulsion was obtained and stored at 4℃ for analysis.

[0042] 1. Emulsion droplet size distribution and size The size distribution and size of the emulsion were measured by a dynamic laser particle size analyzer. Deionized water was used as a dispersant, the refractive index of the emulsion was 1.49, and the particle size of the emulsion was measured by D, which was the volume-weighted average particle size of the emulsion.

[0043] (II) Emulsion zeta potential analysis The emulsion potential was measured using a multi-angle particle size and high-sensitivity Zeta potential analyzer. Before measurement, the emulsion was diluted 100 times with deionized water, the measurement temperature was 20°C, and each sample was measured three times to obtain the average value.

[0044] (III) Rheological properties of emulsion Before measuring the rheological properties, the emulsion needs to be left overnight. The rheological properties of the emulsion are measured according to the method of Example 2 (vi).

[0045] (IV) Storage stability The prepared fresh emulsion was bottled in a 20 mL glass sample bottle, placed naturally indoors for 15 days, and its changes were observed.

[0046] (V) Environmental stability Freshly prepared emulsions with a nanocellulose concentration of 0.6% and a water-oil ratio of 5:5 were used as the research object. The emulsions were treated with different ionic strengths, pH and temperature environments to study their stability. 20 mL of fresh emulsion was diluted with the same volume of 10mM, 50mM, 70 mM, 100mM and 200mM NaCl solutions, respectively, so that the final emulsion contained 25% of the oil phase, and the changes in the stability and physical properties of the emulsion under different ionic strengths were observed and measured. The pH of the emulsion was adjusted with 1 mol / L HCl and NaOH, so that the pH of the emulsion varied in the range of 2-12, and the final emulsion contained 25% of the oil phase. 10 mL of fresh emulsion was placed in a plastic centrifuge tube, and it was placed in a water bath at 20℃, 40℃, 60℃, 80℃ and 100℃ for 30 min, and the changes in the emulsion were observed. Before measuring the physical properties of the emulsion, the sample was left overnight to reach equilibrium.

[0047] (VI) Stabilization of Pickering emulsions with different oil-water ratios Nanocellulose crystals were dispersed in deionized water to make the cellulose content 0.6%. The oil-water ratio was set to 1:9, 3:7, 5:5, 7:3, and the corresponding bran oil was added. Then, the high shear emulsifier was used for shearing at 10000 r / min for 3 min and high pressure homogenization at 20 MPa for 2 min. The Pickering emulsion was obtained and stored at 4°C for analysis.

[0048] Results and Analysis: (1) Effect of different cellulose concentrations on the stability of Pickering emulsions Cellulose nanocrystals treated with ultrasound at 450W for 60min were used as emulsion stabilizers, and the cellulose concentration (0.2%, 0.4%, 0.6%, 0.8% and 1.0%) was adjusted to evaluate the effect of concentration on emulsion formation and stability. Figure 10-12As shown in the figure, after preparing the fresh emulsion, the cellulose concentration of 0.2% quickly showed oil-water stratification and failed to form a stable Pickering emulsion. The rest of the emulsions showed good stability. This may be because the low concentration of cellulose cannot completely cover the oil-water interface, resulting in insufficient stabilization of 50% of the oil phase. With the increase of cellulose concentration, more cellulose particles can be adsorbed on the oil-water interface, which helps to stabilize the Pickering emulsion. The particle size of the emulsion was tested. With the increase of cellulose concentration, the particle size of the fresh emulsion gradually decreased from 9.1 μm to 3.4 μm, indicating that high concentration of cellulose is conducive to the formation of a more stable emulsion.

[0049] (2) Storage stability of Pickering emulsions with different cellulose concentrations Emulsions with cellulose concentrations of 0.2%, 0.4%, 0.6%, 0.8% and 1.0% were prepared. The emulsions were stored at room temperature and observed after 15 days. Fig.13 As shown, with the increase of cellulose concentration, the stability of the emulsion shows an upward trend. The cellulose was photographed and observed after 15 days of storage. The emulsion prepared with 0.2% cellulose concentration had oil phase precipitation on the upper layer, and the emulsion prepared with 0.4% cellulose concentration had obvious water phase precipitation, which proved that low concentration cellulose could not stabilize the emulsion well. Emulsions with a concentration of 0.6% and above have better performance in stabilizing cellulose. It shows that with the increase of cellulose concentration, the stability of the emulsion shows an upward trend. The particle size of the emulsion was tested and increased to varying degrees.

[0050] (3) Effect of different water-oil ratios on the stability of Pickering emulsions The oil-water ratio has a key influence on the stability and characteristics of the emulsion. The present invention sets different water-oil ratios (different ratios) and analyzes the stability of each emulsion at a cellulose concentration of 0.6%. The observation results are as follows Fig.14 It shows that with the increase of oil phase ratio, the droplet size increases from 4.6 μm to 10.6 μm. After 15 days of storage, the 7:3 emulsion showed obvious separation. This change may be caused by the inability of the 7:3 oil-water ratio to effectively cover too many oil droplets during storage. In general, cellulose after ultrasonic treatment can maintain a good and stable emulsion state with 50% or less oil phase.

[0051] (4) Effect of different ultrasonic powers on the stability of cellulose Pickering emulsion Four ultrasonic powers of cellulose were used to stabilize Pickering emulsions, and the stability of each emulsion at 0.6% cellulose concentration was analyzed. Fig.15The results show that the emulsions prepared by the four celluloses have good stability. After storage for 15 days, the emulsions still maintain a good state. The cellulose treated with various ultrasonic powers has a good ability to stabilize the emulsion.

[0052] (5) Effect of different ion concentrations on the stability of Pickering emulsions As shown in Figure 16, when the NaCl concentration increases to 75mM, the droplet size gradually increases from the original 5.3 to 12.5μm. As the NaCl concentration further increases to 200mM, the droplet size increases sharply to 42.8μm. The Zeta potential shows a similar trend to the droplet size. As the NaCl concentration increases, the absolute value of the Zeta potential decreases significantly from 42.5mV to 14.3mV. The emulsion with a NaCl concentration below 75mM can maintain good properties, indicating that the Pickering emulsion stabilized by nanocellulose has a certain ability to resist changes in the ionic environment.

[0053] (6) Effect of different pH values ​​on the stability of Pickering emulsions As shown in Figure 17, the pH value of the emulsion was adjusted. As the pH value increased from 2 to 12, the absolute value of the Zeta potential increased slightly, maintaining good stability. The droplet size was relatively stable, with a small increase, and the droplet size was basically maintained at about 5 μm, which was less affected by the pH change. This shows that the emulsion has good stability in a wide range of pH values ​​of 2-12.

[0054] (7) Effect of different temperatures on the stability of Pickering emulsion like Fig.18 As shown in the figure, during the heat treatment at 20℃-100℃, the particle size of the emulsion remained stable at about 4.8μm, and the absolute value of the Zeta potential remained at about 46 MV, without significant changes. This shows that temperature has little effect on the stability of the emulsion, indicating that the emulsion has excellent thermal stability at 20℃-100℃.

[0055] Example 4 Loading Paeonol Under light-proof conditions, a certain amount of paeonol was weighed and dissolved in peony oil and stirred at room temperature in the dark to completely dissolve. The aqueous phase (cellulose suspension) and the oil phase were mixed at an oil-water ratio of 1:9 (w / w) to prepare an emulsion containing 0.1% (w / w) paeonol in the final emulsion. The emulsions prepared with 150w, 300w, 450w, and 600w nanocellulose were recorded as A-emulsion, B-emulsion, C-emulsion, and D-emulsion, respectively.

[0056] (1) Effect of different ultrasonic conditions on the storage retention rate of cellulose in paeonol like Fig.16 The changes in the retention of paeonol by nanocellulose-stabilized emulsions of various lengths during storage at 20°C for 28 days were presented. The results showed that after 28 days of storage, the retention rates of paeonol in the four emulsions were: 68.86±1.58% for type A, 73.40±2.01% for type B, 75.12±1.31% for type C, and 77.12±1.68% for type D. This shows that shorter nanocellulose can more effectively maintain the content of paeonol. This is because short nanocellulose has a higher surface area coverage of the emulsion and can form a tight interfacial film on the interface to absorb and seal paeonol.

[0057] (2) Effect of emulsion structure on the bioavailability of paeonol in emulsion like Fig. 20 As shown in the figure, the bioavailability of paeonol decreases in the order of: D-emulsion, C-emulsion, B-emulsion and A-emulsion. This also shows that the length of nanocellulose has an effect on the bioavailability of paeonol. When its length increases, the bioavailability of paeonol decreases. Cellulose treated with high ultrasonic power has a higher digestibility, and paeonol dissolved in oil droplets is easier to be released, and more free fatty acids generated can enter the mixed colloid, which can improve the solubility of paeonol in the mixed colloid. After digestion in the stomach, the emulsion droplets in the nanocellulose emulsion aggregate into a mass, making the entire system gel, and this process also leads to changes in the emulsion structure. These changes may limit the decomposition of oil in the mass emulsion, making it difficult to achieve effective paeonol release.

Claims

1. A method for preparing rice bran cellulose nanocrystals, characterized in that: The following steps are involved: (1) crushing and sieving the bran, washing the bran powder with ethanol, and then rinsing and drying to obtain treated bran powder; adding the bran powder to a NaOH solution, stirring, then filtering and collecting the precipitate, washing the precipitate with deionized water, and after the alkaline washing, drying the precipitate to obtain bran particles; (2) Resuspending the bran particles in distilled water; then, adding α-amylase at a ratio of 1:20 (m / v) and stirring at room temperature; after starch hydrolysis, adjusting the pH, adding alkaline protease, heating and stirring, centrifuging the mixture to collect particles, washing with distilled water to obtain an alkaline washed precipitate; adding the dried alkaline washed precipitate to a bleaching solution for bleaching; after the bleaching is completed, filtering and collecting the precipitate, and finally repeatedly washing and filtering with deionized water until the pH of the filtrate is neutral, and drying to obtain bran cellulose; (3) Weighing purified rice bran cellulose, dispersing it in a sulfuric acid solution according to a solid-liquid ratio, and hydrolyzing it; after the hydrolysis is completed, immediately terminating the reaction; removing the supernatant by centrifugation to collect the precipitate, then dialyzing it, and then diluting it with purified water to obtain a cellulose suspension; (4) Take a cellulose suspension, insert a titanium metal ultrasonic probe into the cellulose suspension, and perform ultrasonic treatment to obtain rice bran cellulose nanocrystals.

2. The preparation method according to claim 1, characterized in that: In step (1), the solid-liquid ratio of the bran powder to ethanol is 1:20; the drying temperature is 60°C; the solid-liquid ratio of the bran powder to the NaOH solution is 1:10 (w / v); the concentration of the NaOH solution is 4% (w / v); the stirring treatment is continuous stirring for 2 hours in a 90°C water bath environment; and the drying temperature is 50°C.

3. The preparation method according to claim 1 or 2, characterized in that: In step (2), the bran particles are resuspended in 80° C. distilled water for 1 h; the ratio of the bran particles to α-amylase is 1:20 (m / v); the concentration of the α-amylase is 0.6% (w / v); the stirring time at room temperature is 3 h; after starch hydrolysis, the pH is adjusted to 11; the amount of alkaline protease added is 0.03% (w / w) of the weight of the bran particles; the specification of the alkaline protease is 200 U / mg; and the heating stirring is stirring at 80° C. for 1 h.

4. The preparation method according to claim 1 or 3, characterized in that: In step (2), the composition of the bleaching solution is: 1.7% (w / v) NaClO, 2.7% (w / v) NaOH, 7.5% (v / v) glacial acetic acid, and the balance water; the solid-liquid ratio of the alkaline washing precipitate to the bleaching solution is 1:25 (w / v); and the bleaching treatment is carried out by continuously stirring in a water bath environment at 80°C for 2 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (3), the ratio of the rice bran cellulose to the sulfuric acid solution is 1:15 (w / v); and the mass concentration of the sulfuric acid solution is 62%.

6. The preparation method according to claim 1 or 5, characterized in that: In step (3), the hydrolysis is carried out at 45°C for 30 min; the centrifugation is carried out at 8000 r / min for 10 min; and the dialysis is carried out at a molecular weight of 8000-14000.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (4), the concentration of the cellulose suspension is 0.3%, w / v; the diameter of the titanium metal ultrasonic probe is 15 mm; the conditions of the ultrasonic treatment are: in an ice water bath, the ultrasonic power is 150-600 W, the ultrasonic time is 60 min, and the ultrasonic process is started for 1 s and stopped for 1 s.

8. A rice bran cellulose nanocrystal prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the rice bran cellulose nanocrystals as claimed in claim 8 in Pickering emulsion.

10. Use of the rice bran cellulose nanocrystals as claimed in claim 8 in the preparation of a paeonol-loaded Pickering emulsion.